Pengaruh kredit pajak luar negeri terhadap investasi dan pemenuhan kewajiban pajak wajib pajak dalam negeri - Mubarak, Israul; Cecilia, Putri Engellina; Firdaus, Hafiz Hasbi; Fitriani, Ika Lutfia (Maliki Interdisciplinary Journal, 2024)
PPh 24 is income tax paid or payable abroad on income from abroad received and can be credited in the same tax year. The influence of foreign tax credits on investment and domestic tax compliance has both positive and negative influences. Therefore, stricter supervision by the government is needed, accompanied by publications and education. In this research, the author uses the library research method which combines the results of previous research. The results of this research are that PPH 24 has 2 influences, both positive and negative